Hedonic hunger and food cravings: understanding their role in premenstrual syndrome among nursing students - Kocyigit, Emine; Gumusay, Mehtap; Demirel Ozbek, Yagmur (Frontiers in Public Health, 2025)
BackgroundPremenstrual syndrome (PMS), characterized by physical, psychological, and behavioral symptoms occurring during the luteal phase of the menstrual cycle, affects more than 48% of women of reproductive age worldwide. The aim of the research is to examine the relationships between hedonic hunger, food cravings, and emotional eating in relation to PMS among Turkish female nursing students.MethodThis cross-sectional and descriptive study was conducted on 207 female undergraduate nursing students. Data were obtained using survey and a face-to-face interview method. The questionnaire includes general information, anthropometric measurements, the Premenstrual Syndrome Scale (PMSS), the Power of Food Scale (PFS), the Food Craving Questionnaire-Trait (FCQ-T), and the Emotional Eater Questionnaire (EEQ). Data analysis was performed with IBM SPSS V26 software.ResultsIn total, 169 (81.6%) PMS (+) and 38 (18.4%) PMS (−) female students participated in the study. The mean age was 21.09 ± 2.41 years, and the mean body mass index was 23.3 ± 4.07 kg/m2. The PFS-Tr, FCQ-T and EEQ total scores was positively correlated with PMSS scores. The strongest predictor for hedonic hunger was food cravings, whereas hedonic hunger, PMS, and emotional eating were significant factors for food cravings. PMS was a problem experienced by most of the students. The results indicate that the presence of PMS is associated with increased hedonic hunger, food cravings, and emotional eating tendencies among university students.ConclusionRaising awareness of PMS and conducting nutrition-related trainings for university students would help them get the knowledge and skills they need to manage its symptoms.